1981
DOI: 10.1677/joe.0.0900179
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Prolactin and Progesterone Responses to Mating Are Altered in Aged Rats

Abstract: The effects of varying amounts of copulatory stimulation on patterns of plasma concentrations of prolactin and progesterone were evaluated in 3- and 12-month-old female rats. The 12-month-old group included rats which still exhibited oestrous cycles and rats in persistent vaginal oestrus (PVO). The extent of copulatory stimulation was defined by the number of intromissions received during mating: less than or equal to 5, 15 or greater than 50. Blood samples were drawn over the 8 days after mating through a can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In regularly cycling and in steroid-treated OVX middle-aged females, the LH surge, but not the PRL surge, is attenuated compared to that observed in young animals [50], although some studies suggest that PRL release may also be affected [51]. It has been suggested that the effects of aging on reproduction in the female rodent may, at least in part, involve changes in the rhythmic output of the SCN [52].…”
Section: Discussionmentioning
confidence: 99%
“…In regularly cycling and in steroid-treated OVX middle-aged females, the LH surge, but not the PRL surge, is attenuated compared to that observed in young animals [50], although some studies suggest that PRL release may also be affected [51]. It has been suggested that the effects of aging on reproduction in the female rodent may, at least in part, involve changes in the rhythmic output of the SCN [52].…”
Section: Discussionmentioning
confidence: 99%
“…An initial explanation (Beach and Levinson, 1950) was that they provide necessary sensory stimulation for the male, an idea that is not su orted by subsequent research (Hart, 1978 Spaulding andPeck, 1974). More likely, the spines provide mechanical stimulation necessary for the surges of progesterone and prolactin in the female that ensures impregnation (Hendricks and Blake, 1981). The implication is that simply copulating to ejaculation is not suflkientthat the type of copulatory behavior provided by the male is important for successful reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the basal PRL levels could be suppressed in the HG females, such that additional stimulation is required to reach the necessary PRL threshold for the establishment and maintenance of pregnancy. One such condition is seen in old cyclic female rats, in which the PRL secretory system experiences a decreased sensitivity to the mating stimulus [29]. The HG females used in the present study were not old, but they could have experienced decreased sensitivity to the mating stimulus.…”
Section: Discussionmentioning
confidence: 82%